DENDA AKIBAT PUTUSNYA PEMINANGAN: STUDI KASUS DI JORONG BATANG GADIH NAGARI BATIPUAH BARUAH - Yulia Elfina Rahmi; Yustiloviani Yustiloviani (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The main problem in this study is fine for the innocent party in terminating the proposal, but because he is the one who decides the proposal, he is the one who is fined. From these problems, the question arises, What are the factors that cause the termination of the proposal in Jorong Batang Gadih Nagari Batipuah Baruah, What is the view of Islamic law regarding the implementation of the payment of fines due to the termination of the proposal in Jorong Batang Gadih Nagari Batipuah Baruah, and the implementation of payment of fines as a result of the termination of the proposal. This research is a field research, data or research materials obtained through interviews. This study uses primary data sources and secondary data sources. Data processing was carried out in a qualitative descriptive manner and explained through effective sentences. The results of this study are that first, the factors causing the termination of the proposal in Jorong Batang Gadih Nagari Batipuah Baruah are caused by economic factors, third person, ethics, and time. The view of Islamic law regarding the implementation of payment of fines due to the breakdown of the proposal in Jorong Batang Gadih Nagari Batipuah Baruah, namely the implementation of fines due to the termination of the proposal is not following Islamic law, because in Islamic law it is explained that fines are sanctions or punishments applied in the form of a person's obligation to pay a sum of money imposed as a result of the violation.